2021
DOI: 10.1101/2020.12.30.424791
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Bovine neutrophils release extracellular traps and cooperate with macrophages inMycobacterium aviumsubsp.paratuberculosisclearancein vitro

Abstract: Mycobacterium avium subsp. paratuberculosis (Map) is the underlying pathogen causing bovine paratuberculosis (PTB), an enteric granulomatous disease that mainly affects ruminants and for which an effective treatment is needed. Macrophages are the primary target cells for Map, which survives and replicates intracellularly by inhibiting phagosome maturation. Neutrophils are present at disease sites during the early stages of the infection, but seem to be absent in the late stage, in contrast to healthy tissue. A… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 61 publications
0
7
0
Order By: Relevance
“…The release of NETs is characterized by the immobilization and elimination of pathogens, although their presence could act as a double-edged weapon related to severe collateral tissue damage [30,43,44]. Previous studies have demonstrated the generation of NETs in response to SA [33,45,46], EC [31,47] and Map [35]. In this study, infection of ovine neutrophils with SA resulted in the highest percentage of extracellular DNA.…”
Section: Discussionmentioning
confidence: 60%
See 3 more Smart Citations
“…The release of NETs is characterized by the immobilization and elimination of pathogens, although their presence could act as a double-edged weapon related to severe collateral tissue damage [30,43,44]. Previous studies have demonstrated the generation of NETs in response to SA [33,45,46], EC [31,47] and Map [35]. In this study, infection of ovine neutrophils with SA resulted in the highest percentage of extracellular DNA.…”
Section: Discussionmentioning
confidence: 60%
“…Besides, the action of NETs during paratuberculosis pathogenesis has not been fully elucidated. Bovine neutrophils have been demonstrated to release NETs in response to in vitro Map infection [35]. Here, although in a lesser extent than SA and EC, Map infection also promoted the release of NETs in ovine neutrophils.…”
Section: Discussionmentioning
confidence: 70%
See 2 more Smart Citations
“…We chose to assess the neutrophil responses as alterations in Cxcr4/Cxcl12 signalling would likely impact the mobility and responsiveness of neutrophils to pathogens. Recent studies on the role of the neutrophils in early infection suggest a host-protective response against mycobacteria [40,59], and we hypothesised that these cells may be responsible for the reduced disease burden in miR-206 knockdown embryos. It is, however, likely that the alteration of targets Elmo1 and Timp3 may be contributing to this effect and that role of these genes in mycobacterial infection must be further examined, especially in regard to their involvement in the miR-206/Cxcr4/Cxcl12 signalling axis.…”
Section: Plos Pathogensmentioning
confidence: 99%